2015
DOI: 10.1016/j.visres.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion therapy improves phase-alignment of the cortical response in amblyopia

Abstract: The visual evoked potential (VEP) generated by the amblyopic visual system demonstrates reduced amplitude, prolonged latency, and increased variation in response timing (phase-misalignment). This study examined VEPs before and after occlusion therapy (OT) and whether phase-misalignment can account for the amblyopic VEP deficits. VEPs were recorded to 0.5-4cycles/degree gratings in 10 amblyopic children (2-6years age) before and after OT. Phase-misalignment was measured by Fourier analysis across a limited band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 66 publications
3
15
0
Order By: Relevance
“…[12][13][14] Physiologically, cortical responses driven by stimulation of the amblyopic eye are less synchronized, 17 and their temporal encoding is less reliable. 15,16 Studies of normally sighted people also demonstrate that audition is more temporally precise than vision, 37 and tends to be dominant in processing the temporal dimension of audiovisual events. 23,[38][39][40] Given the normal dominance of audition in temporal audiovisual processing, any amblyopic deficit in auditory temporal resolution would likely have diminished the magnitude of the temporal ventriloquism effect and the sound-induced flash illusion, yet no such diminution was observed in the present study or previously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[12][13][14] Physiologically, cortical responses driven by stimulation of the amblyopic eye are less synchronized, 17 and their temporal encoding is less reliable. 15,16 Studies of normally sighted people also demonstrate that audition is more temporally precise than vision, 37 and tends to be dominant in processing the temporal dimension of audiovisual events. 23,[38][39][40] Given the normal dominance of audition in temporal audiovisual processing, any amblyopic deficit in auditory temporal resolution would likely have diminished the magnitude of the temporal ventriloquism effect and the sound-induced flash illusion, yet no such diminution was observed in the present study or previously.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increased temporal jitter 15,16 and increased latency 41,42 in cortical signals from the amblyopic eye may alter the perceived timing of a visual event such that the probability distribution for the estimate of visual event timing is widened and shifted toward later onset. Miscalibration of visual temporal reliability, induced by amblyopic visual input and crystallized during development, may therefore provide an explanation for the weaker temporal constraints (i.e., wider temporal window) for audiovisual perceptual binding documented in the present study and in prior work on amblyopic multisensory perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that a measure of interocular inhibition was highly accurate in discriminating amblyopic eyes from myopic eyes with or without the presence of refractive correction. With respect to the treatment of amblyopia, Kelly et al (2015) used visually evoked potentials (VEPs) to investigate the effect of occlusion therapy on the cortical response to information from the amblyopic eye. Prior to treatment, amblyopic eye VEPs exhibited a poorer signal-to-noise ratio, a longer latency and increased phase misalignment relative to fellow eye VEPs.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%